2016
DOI: 10.1016/j.jallcom.2016.07.092
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of MgO//Mg interfacial crystal orientations during oxidation: A density functional theory study

Abstract: In this work we use computer simulations to explain the variety of crystal orientations observed at interfaces between MgO and Mg when Mg single crystals are oxidized. Using first-principles density functional theory simulations we investigate the interfacial stability of MgO//Mg interfaces, and find that a combination of interfacial chemical bonding energy and epitaxial strain stored in the oxide layers can change the relative stability of competing MgO//Mg interfaces. We propose that a combination of the oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Meanwhile, some quadrate-like particles are detected near to the tip of the sublimation edge. Both of them are related to the presence of MgO phases, in which the large stress between the interface of Mg and MgO results in the formation of cracks …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, some quadrate-like particles are detected near to the tip of the sublimation edge. Both of them are related to the presence of MgO phases, in which the large stress between the interface of Mg and MgO results in the formation of cracks …”
Section: Resultsmentioning
confidence: 99%
“…Both of them are related to the presence of MgO phases, in which the large stress between the interface of Mg and MgO results in the formation of cracks. 22 In contrast, the surface changes into more active with increasing the e-beam dose to 1 × 10 5 e/nm 2 •s (Figure 3c−f, Movie 3). On the one hand, the exterior amorphous layer slightly shinks with retarding irradiation time, analogous to the sublimation of Mg under a mild e-beam dose.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Statistical mechanics calculations within the HA provide a robust way of calculating the temperature dependences of internal energy and Helmholtz free energy of a solid [16], especially at temperatures far below the melting point [34,35]. We thus use this method to compute the internal energy and the Helmholtz free energy as a function of temperature for the solid argon, from which the value of free energy (FR) at a reference temperature (e.g.…”
Section: Harmonic Approximation Calculations For Solid Argonmentioning
confidence: 99%
“…There have been both experimental and modeling efforts to understand the nucleation of a-Mg on native MgO particles. [13,[16][17][18][19][20][21] Native MgO particles in Mg melts have two distinctive morphologies: octahedron with {1 1 1} surface terminations (denoted as MgO{1 1 1}) and cubic with the {0 0 1} surface terminations (denoted as MgO{0 0 1}). [12,13,[16][17][18][19] Experimental investigations by high-resolution transmission electron microscopy (HRTEM) have confirmed that there exist specific orientation relations (ORs) between the MgO substrates and the solid Mg.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that fcc MgO can act as sites for heterogeneous nucleation of hcp a-Mg. First-principles approaches were used to explore mainly the wetting and adhesion for different crystal orientations between solid a-Mg and MgO. [20][21][22] In order to understand the structural effect on prenucleation at atomic level, Men and Fan [23,24] performed atomistic molecular dynamics (MD) simulations on the atomic ordering in a liquid metal adjacent to a smooth substrate of different lattice misfits. Their simulations showed that the structural effect is strong on the in-plane atomic ordering but weak on the atomic layering in the liquid adjacent to the substrate.…”
Section: Introductionmentioning
confidence: 99%